PENGARUH MODEL PEMBELAJARAN MARIA MONTESSORI TERHADAP PENGEMBANGAN KEDISIPLINAN ANAK USIA 4-5 TAHUN DI TK ISLAM IBNU QOYYIM KEC. MEDAN SELAYANG - Fatma Gustina; Khadijah Khadijah; Fauziah Nasution (Universitas Islam Negeri Sumatera Utara, 2019)
This research was conducted at TK Islam Ibnu Qoyyim, Medan Selayang District. Tthe type of research is experimental research with uses Quasi Experimental Designs. This study aims to determine the influence of Maria Montessori's learning model on the discipline of children in TK Islam Ibnu Qoyyim. The results showed that the Montessori learning model had an effect on the discipline of group A children. The results of the pretest class were 9.3 and the post-test average was 16.80 with the highest post-test 20 and the lowest post-test 12. Class control with an average pre test 9.7 and the average post test 11.7 with the highest value 16 and the lowest value 7. The results of hypothesis testing obtained t count> t table is 18.31> 2.048 with significant numbers. Thus the hypothesis Ho is rejected and Ha is accepted so that it is stated that there is a Significant Effect of Maria Montessori's Learning Model on the Discipline of Group A Children 4-5 Years Old in the TK Islam Ibnu Qoyyim.